A screen of 1, 049 schizophrenia and 30 Alzheimer's‐associated variants for regulatory potential. Issue 1 (10th September 2019) - Myint, Leslie; Wang, Ruihua; Boukas, Leandros; Hansen, Kasper D.; Goff, Loyal A.; Avramopoulos, Dimitrios
Abstract: Recent genome‐wide association studies (GWAS) identified numerous schizophrenia (SZ) and Alzheimer's disease (AD) associated loci, most outside protein‐coding regions and hypothesized to affect gene transcription. We used a massively parallel reporter assay to screen, 1, 049 SZ and 30 AD variants in 64 and nine loci, respectively for allele differences in driving reporter gene expression. A library of synthetic oligonucleotides assaying each allele five times was transfected into K562 chronic myelogenous leukemia lymphoblasts and SK‐SY5Y human neuroblastoma cells. One hundred forty eight variants showed allelic differences in K562 and 53 in SK‐SY5Y cells, on average 2.6 variants per locus. Nine showed significant differences in both lines, a modest overlap reflecting different regulatory landscapes of these lines that also differ significantly in chromatin marks. Eight of nine were in the same direction. We observe no preference for risk alleles to increase or decrease expression. We find a positive correlation between the number of SNPs in linkage disequilibrium and the proportion of functional SNPs supporting combinatorial effects that may lead to haplotype selection. Our results prioritize future functional follow up of disease associated SNPs to determine the driver GWAS variant(s), at each locus and enhance our understanding of gene regulation dynamics.